Design of Electronic Expanded Valve (EEV) Control System Based On the STC89S52 Microcontroller - Wu Junyun; Ge Rongjian; Guo Mingzhu; Qiu Huixiang (Zhileng xuebao)
Aiming at the control problems of evaporator superheating in the household Variable frequency air conditioner, the Electronic Expanded Valve (EEV) control system was investigated based on a dead band integral-separation PID control algorithm and the STC89S52 single-chip microcontroller as the control core. And the control system principle, the hardware circuit and the software design are expounded too. The experimental results of household air conditioning showed that the EEV control system had the characteristics of static accuracy, adaptability, reliability, and anti-interference.